Elemental Composition and Morphometry of Rhyssoplax olivacea (Polyplacophora): Part I—Radula and Valves - Thomas Mygdalias; Anastasios Varkoulis; Konstantinos Voulgaris; Stefanos Zaoutsos; Dimitris Vafidis (Journal of Marine Science and Engineering)
Rhyssoplax olivacea is the most common Mediterranean polyplacophoran species; however, no information exists regarding the functionality of its skeleton. The present study describes allometric trends related to its valves and radula and examines their chemical composition using specimens from the Aegean Sea, eastern Mediterranean Sea. Differences in valve width and thickness were found among all three valves; in particular, the intermediate valve had a significantly shorter length compared to the two terminal ones. The intermediate valve exhibited different trends for valve length to valve width and valve length to valve thickness compared to the terminal valves. However, all valve morphometrics to body length appeared to adhere to a shared trend. The radula to body length exhibited positive allometry. Regarding the elemental composition, all three valves appeared to have similar elemental compositions; however, the element concentrations in the radula differed with the tooth type. Iron was always the dominant element, with the highest values reported for the major lateral tooth (83% wt%). This study provides valuable insights into the different aspects of the skeleton of R. olivacea, enabling future research to focus on the skeletal functionality from evolutionary and ecological perspectives.